IMPLEMENTASI TUGAS KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PELAYANAN PENDIDIKAN DI SMA NEGERI 2 KABUPATEN SARMI - ALTON MATAPUTUN (Universitas Cenderawasih, 2020)
The purposes of this study were to describe the implementation of school committee tasks, which are (1) giving consideration in determining and implementing educational policies, (2) raising funds and educational resources, (3) evaluating education services in schools, and (4) following up on community aspirations. This study also described the supporting factors and obstacles in the implementation of school committee tasks in improving the quality of education services. This was a qualitative descriptive research based on a study case using Huberman and Miles model. The informants consisted of school committee, parents, the headmaster, teachers and students. The results of the research were (1) school committee had implemented the duties at the school even though it is not at the ideal degree, (2) the fundraising activities still depended on internal efforts of the school, (3) particularly the school committee has provided considerations on school matters, decision making, and monitoring of school services, (4) The school committee had followed up complaints, targets, criticisms, and aspirations from the students, parents and societies as well as evaluate school performance. The second research resulted regarding the supporting factors of school committee in implementing their duties is the human resource availability in the committee, facilities and supportive school environment. However, the hindrances such as inactive members of the committee, lack of understanding on roles of school committee, and the perspectives of parents on free education system. Key Words: School Committee, Quality, Education Services